Análise acerca dos limites da liberdade de expressão política no âmbito dos eventos olímpicos Rio/2016 - Coelho Neta, Joana D'arc Fernandes (Universidade Federal Rural do Semi-Árido, 2017)
This paper proposes to analyze the limits of freedom of expression in the Olympic Games held in the city of Rio de Janeiro in 2016. Such games were regulated by Federal Law 13,284, of 2016, which, in Its article 28 establishes some limitations to the aforementioned constitutional law, in order to ensure the proper functioning of the event in question. In the course of the games, peaceful demonstrations of political nature inside the venues of competitions and presentations were forbidden. In this context, the study seeks to establish a relationship between politics and sports, emphasizing that, throughout history, these have always been inseparable. It also addresses the definition of freedom of expression and dignity of the human person, stating in which situations such fundamental rights may be liable to limitation due to the socalled rights collisions. In addition, an explanation is given as to what would be law-measure, such as the one that regulated the Olympic games, demonstrating the international interferences / influences it underwent, doing it under the prism of the transconstitutionalism, to only then enter into the merits of the constitutionality of the Law in question and of the acts practiced by the Public Power using it as legal support. That is, it is an analysis of the constitutionality of the interpretation given to the aforementioned law by public agents. The research carried out has a theoretical, bibliographical and documentary character, and some documents reveal the experience (empiria) of news events that occurred during the Olympics. Thus, it was developed based on literature on the subject, as well as on legislation and related judgments. Finally, it is concluded that the prohibition of political manifestations was not in accordance with the legal text nor as stated in the Constitution of the Federative Republic of Brazil of 1988, since they consisted of a disproportionate limitation on freedom of expression, violating the dignity of the Human person and causing immeasurable damage to the democratic regime.
Monografia
Keywords: Direito constitucional; Liberdade de expressão política; Dignidade da pessoa humana; Olimpíadas Rio/2016; CIENCIAS SOCIAIS APLICADAS::DIREITO